2000
DOI: 10.1128/iai.68.2.815-823.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Gene Cluster ofEnterococcus faecalisInvolved in Polysaccharide Biosynthesis

Abstract: Previously, we described a gene cluster of Enterococcus faecalis OG1RF that produced an antigenic polysaccharide when cloned in Escherichia coli. The polysaccharide antigen was not detectable in E. faecalis strains, however. Here, we show by reverse transcriptase-PCR that the 16 genes in this region are transcribed in OG1RF. Gene disruption of orfde4, encoding a putative glycosyl transferase, and orfde6, a putative dTDPrhamnose biosynthesis gene, generated two OG1RF mutants. The mutants showed delayed killing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 26 publications
3
107
0
4
Order By: Relevance
“…While we have not characterized Epa biochemically, Hancock and Gilmore were able to detect three different cell wall carbohydrates in E. faecalis: a type-specific capsular polysaccharide, a rhamnopolysaccharide (possibly Epa), and a polymer likely representing an integral cell wall teichoic acid (7). Their model, in agreement with our earlier observations (27), suggests that the Epa polysaccharide is not on the cell surface, at least in vitro; however, Epa may be important for the overall integrity of membrane and/or cell wall structures, or conceivably, it could be exposed on the surface in vivo. Our present results showed that there was no detectable translocation of the epa mutant TX5179 across the T84 monolayers and that the translocation efficiency of the epa mutant TX5180 was lower (about 10-fold) than that of the wild-type strain OG1RF, indicating that some epa genes, especially orfde4, are important for successful translocation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…While we have not characterized Epa biochemically, Hancock and Gilmore were able to detect three different cell wall carbohydrates in E. faecalis: a type-specific capsular polysaccharide, a rhamnopolysaccharide (possibly Epa), and a polymer likely representing an integral cell wall teichoic acid (7). Their model, in agreement with our earlier observations (27), suggests that the Epa polysaccharide is not on the cell surface, at least in vitro; however, Epa may be important for the overall integrity of membrane and/or cell wall structures, or conceivably, it could be exposed on the surface in vivo. Our present results showed that there was no detectable translocation of the epa mutant TX5179 across the T84 monolayers and that the translocation efficiency of the epa mutant TX5180 was lower (about 10-fold) than that of the wild-type strain OG1RF, indicating that some epa genes, especially orfde4, are important for successful translocation.…”
Section: Discussionsupporting
confidence: 80%
“…To further confirm the importance of epa genes for translocation, the epa mutant with a disruption in orfde4, TX5179, was complemented with extrachromosomal orfde4 and its downstream gene orfde5 (both genes are likely to be in the same operon [27]). The polysaccharide content of the complemented strain was compared with that of the mutant (TX5179) and wild-type OG1RF, and the polysaccharide smear missing in the mutant TX5179 appeared in the complemented strain, which showed a polysaccharide pattern similar to that of the wild-type strain OG1RF; the pAT18 shuttle vector did not affect the polysaccharide component (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In gram-positive bacteria, genes highly similar to those involved in the biogenesis of capsular polysaccharide and LPS are found (267,534). In B. subtilis, limited expression of the tagGH genes leads to anomalous morphology and a decrease in cell wall galactosamine and phosphate, two components of teichoic acids.…”
Section: Biogenesis Of Extracellular Polysaccharidesmentioning
confidence: 99%